Hubungan Pengetahuan Ibu Terhadap Perawatan Nifas di Puskesmas Talang Gading Palembang Tahun 2020 - Yazika Rimbawati; Sasono Mardiono; Putu Lusita Nati Indriani; Alkhusari A (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
According to a preliminary study conducted by researchers that out of 5 postpartum mothers said 5 of these mothers 3 postpartum mothers had less knowledge and 2 postpartum mothers had sufficient knowledge 4 out of 5 postpartum mothers often carried out personal hygiene by changing pads 2 times a day and from 5 mothers 1 postpartum did not do personal hygiene, the mother said she was lazy and didn't have time because she was too busy taking care of her baby. The general objective is to find out the relationship between maternal knowledge and postpartum care at the Talang Gading Palembang Health Center in 2020. The type of research used is an analytic survey with a cross sectional study approach to look at the momentary relationship between the independent and dependent variables. Populasai are all research subjects or objects studied (Notoatmodjo, 2019). The population in this study were all mothers living in the working area of the Talang Gading Health Center. that of the 22 respondents who had poor knowledge of experiencing gastritis, there were 22 respondents (32.8%) who did not experience gastritis. From the results of the Chi-Square statistical test, a p value of 0.000 (Î± = â‰¤ 0.05) was obtained, meaning that there was a significant relationship between maternal knowledge and the incidence of postpartum care. Thus the hypothesis that there is a relationship between maternal knowledge and postpartum care is statistically proven. Based on the results of research on